Genetic and environmental factors affecting trypanosome prevalence and parasitaemia in livestock - D'Ieteren, G.D.M.; Awuome, K.; Bokovi, K.; Chema, S.; Colardelle, C.; Coulibaly, L.; Defly, A.; Feron, A.; Grundler, G.; Handlos, Michael; Hecker, P.; Itty, P.; et al. (ILCA/ILRAD, 1988)
Presents results of a consolidated study on genetic and environmental factors affecting trypanosome prevalence and parasitaemia in livestock from the ten sites of the African Trypanotolerance Network. Includes data on prevalence in sheep, goats and cattle, prevalence in three age classes of cattle, sheep, prevalence of female physiological-status classes in cattle, prevalence when gestating and not gestating.